Mitochondrial Complex I Core Protein Regulates cAMP Signaling via Phosphodiesterase Pde2 and NAD Homeostasis in Candida albicans - She, Xiaodong; Zhang, Lulu; Peng, Jingwen; Zhang, Jingyun; Li, Hongbin; Zhang, Pengyi; Calderone, Richard; Liu, Weida; Li, Dongmei (Frontiers in Microbiology, 2020)
The cAMP/PKA pathway of C. albicans responds to nutrient availability to coordinate a series of cellular processes for its replication and survival. The elevation of cAMP for PKA signaling must be both transitory and tightly regulated. Otherwise, any abnormal cAMP/PKA pathway would disrupt metabolic potential, ergosterol synthesis, and promote a stress response. One possible mechanism for controlling cAMP levels is direct induction of the phosphodiesterase PDE2 gene by cAMP itself. Our earlier studies have shown that most single gene deletion mutants of the mitochondrial electron transport chain (ETC) complex I (CI) are hypersensitive to fluconazole. To understand the fluconazole hypersensitivity observed in these mutants, we focused upon the cAMP/PKA-mediated ergosterol synthesis in CI mutants. Two groups of the ETC mutants were used in this study. Group I includes CI mutants. Group II is comprised of CIII- and CIV- mutants; group II mutants are known to have a greater respiratory loss. All mutants are not identical in cAMP/PKA-mediated ergosterol response. We found that ergosterol levels are decreased by 47.3% in the ndh51Δ (CI core subunit protein) and by 23.5% in goa1Δ (CI regulator mutant). Both mutants exhibited a greater reduction of cAMP and excessive trehalose production than other mutants. Despite the normal cAMP level, ergosterol content decreased by 33.0% in the CIII mutant qce1Δ as well, thereby displaying a cAMP/PKA-independent ergosterol response. While the two CI mutants have some unique cAMP/PKA-mediated ergosterol responses, we found that the degree of cAMP reduction correlates linearly with a decrease in total NAD levels in all mutants, particularly in the 7 CI mutants. Mechanism study demonstrates that overactive PDE2 and cPDE activity must be the cause of the suppressive cAMP-mediated ergosterol response in the ndh51Δ and goa1Δ. While the purpose of this study is to understand the impact of ETC proteins on pathogenesis-associated cellular events, our results reveal the importance of Ndh51p in the regulation of the cAMP/PKA pathway through Pde2p inhibition in normal physiological environments. As a direct link between Ndh51p and Pde2p remains elusive, we suggest that Ndh51p participates in NAD homeostasis that might regulate Pde2p activity for the optimal cAMP pathway state.